A likkle Miss Lou : how Jamaican poet Louise Bennett Coverley found her voice - Hohn, Nadia L. (Owlkids Books, 2019)
"Miss Lou" is widely credited as having helped Jamaican Patois recognized as a "nation language." Thanks to her writing and her work in TV and radio, Jamaican Patois was embraced internationally and she created spaces for poets like Mutabaruka and Linton Kwesi Johnson and singers like Bob Marley and Harry Belafonte to centralize and popularize Jamaican English, Creole, patois in their work. This picture book manuscript focuses on a young Miss Lou who is struggling to find her voice, caught as she is between writing "lines of words like tight cornrows" or writing the words that beat "in time with her heart." On one level, this is a wonderful story of an important figure in Jamaica's cultural legacy. On another level, this is a universal story of a child finding and trusting her own voice. End matter includes a brief biography of Miss Lou, covering her life and influence following this story--including the fact that Miss Lou spent the last 20 years of her life in Canada. There is also a glossary to help readers less familiar with Jamaican patois."--